Penerapan Model Pembelajaran Clis (Children’s Learning In Science) Untuk Meningkatkatkan Hasil Belajar Siswa Kelas XI SMA Negeri 3 Kota Bima - Mayangsari, Ita; Rahmawati, Eka; Subhan, Muhammad (Universitas Nggusuwaru, 2024)
Developing students' ideas or notions in learning activities by reconstructing them from observations through experiments is an important thing to do so that student learning outcomes can be achieved. This learning is known as the CLIS (Children Learning in Science) learning model. This research aims to determine the effect of implementing the CLIS (Children Learning In Science) learning model on the learning outcomes of class XI students at SMAN 3 Kota Bima. This research uses a quantitative approach and a quasi-experimental method with a pretest and posttest design. This research sample used two classes XI MIPA 3 and XI MIPA 4 totaling 62 students with data collection techniques using questionnaires and multiple choice questions tests. The research data were analyzed using tests for normality, homogeneity, average standard deviation and independent sample T test. The results of the research showed that the average standard deviation of learning outcomes for experimental class students was 69.16 and that of the control class was 42.32. Meanwhile, the t-test obtained the Asymp value. Sig. (2-tailed) of 0.00 < 0.05. If the asymp value is sig. <0.05 then the hypothesis is accepted (Ho is rejected). which means there is a significant difference in student learning outcomes between the experimental class and the control class